Assessment of Drug Utilization Pattern of Chemotherapeutic Agents and its Cost Analysis in a Day Care Unit of a Tertiary Care Hospital: An Observational Study - Shah, Rekha; Mandal, Prem Kumar; Mishra, Anjali; Yadav, Rajesh; Yadav, Nabin Kumar (Journal of Nobel Medical College, 2025)
Background: Cancer remains a leading cause of mortality worldwide, with increasing incidence and significant treatment costs, particularly in developing countries like Nepal. Main objective of this study is to evaluate the utilization pattern and cost assessment of chemotherapeutic agents among cancer patients at Birat Medical College Teaching Hospital, Nepal. Materials and Methods: A cross-sectional study was conducted from 26 May to 26 Oct 2024, enrolling 153 cancer patients receiving chemotherapy in a tertiary care hospital in Eastern Nepal. Data on demographics, cancer types, prescribed anticancer medications and associated costs were collected. It was analyzed using descriptive statistics and WHO prescribing indicators. Results: The majority number of patients were female 35 (22.87%) aged between 60-69 years. Breast 26 (16.99%) and lung cancer 25 (16.33%) were the most prevalent. Alkylating agents, antimetabolites and taxanes were the most frequently prescribed drugs. The average number of medications per prescription was 5.29, with chemotherapeutic agents constituting 1.82% and antibiotics 0.01%. Approximately 76.50% of drugs were prescribed by generic name, and 82.86% were from the National Essential Medicine list. The average daily cost of chemotherapy was NPR 927865 (62). Conclusion: Breast and lung cancer were most common in the age groups 60–69 years. Chemotherapy predominantly involved alkylating agents, antimetabolites, and taxanes. Monoclonal antibodies were less frequently used but highly expensive. Prescribing practices largely followed rational drug-use indicators.